Analysis of Electric Arc Furnace Lining Regeneration Process - F.U. Odilov, F.U. Odilov; K.Kh. Abdullaev, K.Kh. Abdullaev; N.X. Tadjiev, N.X. Tadjiev; V.B. Hamroev, V.B. Hamroev; M.N. Gaybullaev, I.T. Tuxtaboev., (Academicia Globe: Inderscience Research, 2020)
In this article, it is important to choose the inner layer of the furnace when melting steel alloy. Magnesite bricks were used as refractory materials for the lining of the basic furnace. Corroded areas of the furnace lining were restored by spraying previously used firebrick powder and pulverized slag mixture into the hot furnace lining, and the service life of the furnace lining was increased.